Group A Streptococcus Infection in Children : Literature Review - Tjiu Ritonga, Christian Martin (International Journal of Scientific Research and Management (IJSRM), 2023)
Streptococci are a large and diverse group of gram-positive cocci that grow in pairs or chains. Invasive group A Streptococcus infection (GAS) is associated with significant morbidity and mortality. The mechanism for spreading Streptococcus from one person to another and one part of the body to another part of the body varies according to the clinical manifestations of the infection. Group A Streptococcus infection, consisting of non-invasive gas infection and invasive gas infection. Generally, for non-severe infections due to group A Streptococcus is good with very low morbidity and mortality rates. On the other hand, the more invasive and severe infections caused by group A Streptococcus carry with them significant mortality and morbidity rates. The purpose of writing this literature review is to improve understanding and treatment of group A streptococcal infections in children so that the mortality and morbidity associated with this infection can be reduced.